2015
DOI: 10.1115/1.4028985
|View full text |Cite
|
Sign up to set email alerts
|

The In Situ Mechanics of Trabecular Bone Marrow: The Potential for Mechanobiological Response

Abstract: Bone adapts to habitual loading through mechanobiological signaling. Osteocytes are the primary mechanical sensors in bone, upregulating osteogenic factors and downregulating osteoinhibitors, and recruiting osteoclasts to resorb bone in response to microdamage accumulation. However, most of the cell populations of the bone marrow niche,which are intimately involved with bone remodeling as the source of bone osteoblast and osteoclast progenitors, are also mechanosensitive. We hypothesized that the deformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 62 publications
(67 reference statements)
3
30
0
2
Order By: Relevance
“…This is in agreement with previous studies, 3,13 although a different trend has been observed elsewhere. 30 The aim of this study was to assess whether physiological compression of trabecular bone generates shear stress within the bone marrow which stimulates new bone growth. It was found within the computational models of the sample specific geometries that shear stress of sufficient magnitude to produce an osteogenic response in MSCs was indeed generated during physiological compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with previous studies, 3,13 although a different trend has been observed elsewhere. 30 The aim of this study was to assess whether physiological compression of trabecular bone generates shear stress within the bone marrow which stimulates new bone growth. It was found within the computational models of the sample specific geometries that shear stress of sufficient magnitude to produce an osteogenic response in MSCs was indeed generated during physiological compression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the shear stress generated in marrow can be of significant magnitude to stimulate an osteogenic response in the bone marrow cells. 3,4,13,16,30,42 The magnitude of shear stress required to generate an osteogenic responses in MSCs and pre-osteoblastic cells in vitro is commonly reported to range between 0.1 and 1 Pa. 1,2,11 Other studies have suggested a lower threshold <0.05 Pa 10,39 and have demonstrated no significant difference in the osteogenic response between osteoblastic cells exposed to either 0.06 or 0.6 Pa. 33 However, the response of marrow cells to this shear stress generated during physiological loading has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Second, these data indicate that MSCs in the humerus were less responsive to mechanical signals, either because of reduced cellular mechanosensitivity per se (Volk et al, 2012), or perhaps due to aspects of the marrow niche (e.g. adjacency to hematopoietic stem cells, higher concentration of adipocytes, marrow viscosity) that confounded the ability of MSCs to commit to an osteoblast lineage (Adler et al, 2014;Metzger et al, 2015). These interpretations must be considered with caution, because changes in MSC numbers alone are not a direct indication of differentiation activity toward osteoblast production, and we did not directly show here that osteoblast numbers increased with exercise treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, estimated shear stress in the marrow near individual trabeculae is 0.5 to 2 Pa [33,37]. In some cases, shear stress may reach up to 5 Pa when the marrow is modeled as a highly viscous material [38]. Using bone explants, Verbruggen et al [39, 40••] recently showed that application of uniaxial compressive strains of up to 3000 με resulted in membrane strains in osteocytes and osteoblasts of up to 30,000 and 25,000 με, respectively, a 10× amplification.…”
Section: Mechanical Signals Generated During Daily Activitiesmentioning
confidence: 99%